ANALISIS SISTEM PENYALIRAN TAMBANG BIJIH NIKEL PADA PT. BUANA CELEBES KECAMATAN MALILI KABUPATEN LUWU TIMUR PROVINSI SULAWESI SELATAN - Calfien Paonganan K; Gina Audina P Alhabsyi; Hendra Sani (Journal Teknik Dan Teknologi, 2024)
PT. Buana Celebes is one of the companies engaged in nickel ore mining business located in Malili district, East Luwu regency, South Sulawesi province. Mining operations arecarriedout by open-pit mining system ( Surface Mining) with open cut method. The purpose of this study istofind out the system of mining that is applied, knowing the total amount of water discharge that enters the deposition pond and to find out the volume of precipitation ponds in the mining area. Basedonthe resultsof researchs istemcopying usedin PT. Buana Celebes is system drainage that is to prevent theentry of water into the mine. At the pit location E Block E2 has 1 (One) precipitation pool with a precipitation pool area of 38,196 m² with 2 (Two) channels with the length of each channel I of 220 m and channel II of 85 m.The amount of runoff discharge in the Pit E area of Block E2 is3,185m3 and the total volume of the deposition pool is 114,588 m3/s.